Konsep Ketuhanan Perspektif Agnostisisme: Studi Kasus Mahasiswa STIBA Ar Raayah Sukabumi - Abdul Halim Muhammad; Nidaul Jannah; Musa Al Faiz; Ramadhan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The existence of God and religion has always been a debate throughout the history of mankind giving birth to various different views, one of which is Agnostic. The existence of agnostics in Indonesia is a phenomenon that is quite unique to trace even though the number of agnostics cannot be ascertained, because every Indonesian citizen is required to embrace one of the six official religions. Therefore, the urgency to understand the concept of Godhood from an Agnostic perspective is very important. This research aims to analyze and explain the concept of agnostic divinity according to STIBA Ar Raayah Sukabumi students, understand how the attitude and implications of STIBA Ar Raayah Sukabumi students towards the concept of agnostic divinity by applying a qualitative approach and descriptive methods. Data were collected using questionnaire techniques and in-depth interviews. The results of the study showed that the respondents' understanding of the concept of Agnostic divinity was quite good, this was evidenced by their answers, the majority of which were in accordance with the definitions of experts. The attitude of the respondents towards the concept of Agnostic divinity is that the majority of respondents are negative about the concept of Agnostic divinity so that it has a positive impact on the spiritual power that they believe that God exists and must be worshipped. Meanwhile, the implications of the concept of Agnostic divinity in the lives of respondents have a great impact on their increasing steadfastness and belief that encourages them to carry out the obligations of a Muslim every day.